Job Satisfaction, Organizational Commitment, and Turnover Intention of Online Teachers in the K-12 Setting - Larkin, Ingle; Brantley-Dias, Laurie; Lokey-Vega, Anissa (Online Learning, 2016)
The purpose of this study was to measure and explore factors influencing K-12 online teachers’ job satisfaction, organizational commitment, and turnover intentions. Using Maslow’s Hierarchy of Needs (1954), Herzberg’s Two-Factor Theory of Satisfaction (1959, 1968), Meyer and Allen’s measure of Organizational Commitment (1997), and Fishbein and Ajzen’s Theory of Reasoned Action and Planned Behavior (1975), this mixed-methods study was conducted in public, private, charter, for-profit, and not-for-profit K-12 online schools in a single Southeastern state. The researchers used a sequential explanatory design by collecting and analyzing quantitative data and then qualitative data in two consecutive phases. Phase I included a 74-item survey with responses from 108 participants. Results revealed that K-12 online teachers have a moderate to high level of job satisfaction, which corresponds to their affective commitment to their organization and their intent to remain teaching in the online setting in the immediate, intermediate, and long-term future. Participants identified flexibility, meeting student needs, technical support, and their professional community as the most satisfying aspects of their jobs. Compensation, workload, missing face-to-face interaction with students, and unmotivated students were identified as least satisfying aspects of their work. In Phase II, eight qualitative focus group interviews were conducted and analyzed using constant comparative methods; these findings confirmed and illuminated quantitative results from Phase I. This study informs K-12 online school leaders, policymakers, and researchers of statistically significant variables that influence K-12 online teacher satisfaction, commitment, and retention.